An Approach to Human-Animal Relationships in Galician Literature - Acuña Trabazo, Ana (Madrygal. Revista de Estudios Gallegos, 2021)
This article aims to be an approach to the relationship between human and non-human animals in different authors and works of Galician literature from an ecocritical pespective. Through the texts the separation between human and non-human animals is exemplified in contexts marked by domination, the human-animal interconnection is illustrated, and finally the plurisensory of the non-human animal is shown. Essays with real oral testimonies are also added that focus on zoe bio separation in situations of extreme violence.